A method for preparing activated carbon from coal gasification slag
Patent Information
- Application Number
- CN202410571450.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-05-09
AI Technical Summary
[0008]综合现有文献资料,未见有煤气化渣经酸溶提取酸溶物、碱溶回收硅制备水玻璃后碱残渣进一步纯化、改性制备活性炭报导
[0019]与现有技术相比,本发明针对煤气化渣含炭量高、提取无机矿物后固废以有机物炭为主的特点,增加煤气化渣多元素提取后固废利用价值,提升了煤气化渣综合利用的经济效益。本发明制备的活性炭性能指标最低达到T/QGCML 205—2021产品标准的要求,实现了固废再利用。本发明提升了煤气化渣多元素提取残渣的附加值,保障了煤气化渣资源化综合利用的经济性和可行性。
Smart Images

Figure CN118439609B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of comprehensive utilization of industrial solid waste resources and environmental protection technology, specifically relating to a method for preparing activated carbon from coal gasification slag. Background Technology
[0002] Chinese invention patent CN202210811727.2 discloses a method for preparing activated carbon from coal gasification fine ash based on NaOH-HCl atmospheric pressure hydrothermal method. The method is characterized by the following steps: 1) mixing fine coal gasification ash and NaOH at a mass ratio of 1:5, adding distilled water and mixing evenly to obtain a reaction system, heating the reaction system to 95°C and hydrothermally treating it for 6 hours, then filtering, washing and drying the filtered solid to obtain an alkali-treated sample; 2) mixing the alkali-treated sample with a 10% HCl solution at a mass ratio of 1:5, then hydrothermally treating it for 3 hours under normal pressure and a temperature of 60°C, filtering after the reaction, washing and drying the filtered solid to obtain a carbon-rich product; 3) mixing the carbon-rich product with an activator evenly, heating the mixture to a temperature of 400°C to 800°C under a specific atmosphere and a heating rate of 5°C / min to 15°C / min, and then activating it for 0.5 hours to 2 hours under a specific atmosphere and a temperature of 400°C to 800°C to obtain activated carbon.
[0003] Chinese invention patent CN202210812544.2 discloses a method for preparing activated carbon for supercapacitors using coal gasification fine ash. The method is characterized by the following steps: 1) Adding coal gasification fine ash to an HCl solution for isothermal acid washing, followed by filtration, washing, and drying to obtain the isothermal acid-washed product; 2) Adding the isothermal acid-washed product to a 20% (w / w) HF solution, maintaining the temperature at 60°C for 3 hours, followed by filtration, washing, and drying to obtain a residual carbon sample; 3) Mixing the residual carbon sample with an activator uniformly, then placing it in a horizontal tube furnace at 800°C, and activating it for 1 hour under a specific atmosphere and at 800°C; the mass ratio of the residual carbon sample to the activator is 1:5; the specific atmosphere is N2, and the flow rate of the specific atmosphere is 200 mL / min; the activator is KOH.
[0004] Chinese invention patent CN 202010551411.5 discloses a method for preparing magnetic activated carbon NaX molecular sieve composite material using coal gasification fine slag as raw material. The specific process is as follows: 1) Solid alkali and coal gasification fine slag are mixed evenly at a mass ratio of 1:2 and placed in a tubular furnace. Argon gas is first introduced at a flow rate of 200 mL / min until the temperature reaches 600℃, then water vapor is introduced at a flow rate of 0.5 mL / (min·g), and the temperature is raised to 700℃. The reaction time is 1 hour to activate the carbonaceous components in the gasification fine slag with water vapor to obtain a mixed product; 2) 7.6 g NaOH and 2.7 g Al(OH)3 are weighed and dissolved in 60 mL of water, heated and stirred for 3 hours, and then 10 g NaSiO3·9H2 is added. O is slowly added to the above solution and stirred at room temperature for 1 hour to obtain an amorphous seed crystal guiding agent; 3) The mixed product obtained in step 2), a certain amount of deionized water and 1 mL of guiding agent solution are thoroughly mixed and stirred at room temperature for 2 hours, and then allowed to stand for 12 hours; 4) The mixed solution is transferred to a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120°C for 12 hours. The solid product is filtered, washed until neutral and dried in an oven at 100°C to obtain a magnetic activated carbon NaX molecular sieve composite material. The specific surface area of this composite material is 400.66 m2 / g, the saturation magnetization is 39.16 emu / g, and the magnetization is effective against Cu in wastewater. 2+ The adsorption rate is 99.4%.
[0005] Chinese invention patent CN 201710154400.1 discloses a method for preparing adsorbent materials using coal gasification fine slag and the resulting adsorbent materials. The method includes: 1) taking an appropriate amount of coal gasification fine slag and adding water to prepare a coal gasification fine slag slurry with a solid content of 10-30 wt%; 2) thoroughly stirring the slurry prepared in step 1), and then separating it by gravity cyclone separation to obtain a carbon-rich composite slurry with a carbon content of over 60 wt% in the solid phase; 3) wet ball milling the carbon-rich composite slurry, followed by solid-liquid separation and drying to obtain a carbon-rich composite powder; 4) activating the obtained carbon-rich composite powder using a steam activation method, with the activation temperature at 700-800℃ and the activation time at 10-60 min, to obtain the adsorbent material.
[0006] Chinese invention patent CN 202211425157.X discloses a method for preparing adsorbent materials using coal gasification fine slag. The steps are as follows: 1) Dry the coal gasification fine slag, add water and 20% KOH, mix thoroughly to form a slurry; 2) Dry the slurry, controlling the moisture content of the dried fine slag; 3) Heat the dried product in the absence of air; 4) Dissolve the dried product in water, add dilute hydrochloric acid and stir slowly, then filter and dry to obtain a coal gasification ash-based adsorbent material. The specific surface area of the adsorbent material reaches 360 m². 2 / g, with a benzene adsorption value of 300mg / g.
[0007] Chinese invention patent CN 202310243055.4 discloses a granular coal gasification fine slag-based adsorbent material, its preparation method, and its application. The method comprises the following steps: 1) sequentially subjecting the coal gasification fine slag to acid and alkali pretreatment to obtain acid- and alkali-treated coal gasification fine slag; pulverizing one or more of waste cotton cloth, linen cloth, waste cotton fiber, waste wood chips, and coconut shells to obtain a doped powder; 2) mixing the doped powder with coal gasification fine slag with a moisture content ≤20% to obtain a composite coal gasification fine slag. 3) Add a modification solution to the composite coal gasification fine slag to perform hydrophobic modification; 4) Add the hydrophobically modified composite coal gasification fine slag to a liquid binder, then mix in a silane coupling agent, stir and mix to make the water content of the mixture 10%-20%, then granulate it under an extrusion pressure of 0.5-5MPa to obtain solid columnar, hollow columnar, spherical, ellipsoidal, square, sheet-like or positive porous channel granular adsorbent material, and finally perform heat treatment.
[0008] Based on existing literature, there are no reports of further purification and modification of the alkaline residue after coal gasification slag is prepared by acid extraction of acid-soluble substances, alkali recovery of silicon, and preparation of water glass, and then modified to prepare activated carbon. Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for further purifying and modifying the alkaline residue after coal gasification slag has undergone acid extraction of acid-soluble substances, alkali recovery of silicon to prepare water glass, and then preparing activated carbon. This invention is achieved through the following technical solution:
[0010] A method for preparing activated carbon from coal gasification slag includes the following steps:
[0011] (1) Acid dissolution: Acid-soluble substances such as calcium, iron, aluminum, magnesium and alkali metals in coal gasification slag are dissolved with hydrochloric acid, and acid slag is obtained by filtration, separation and washing. The reaction conditions are: hydrochloric acid is the theoretical amount of all acid-soluble substances in gasification slag, liquid-solid ratio is 4:1, reaction temperature is 80℃ and reaction time is 3h.
[0012] (2) Alkali dissolution: Alkali is added to the acid residue and allowed to react fully, so that most of the amorphous silicon and a small amount of α-type silicon dioxide in the acid residue are transferred into the alkaline solution. After separation and washing, alkaline residue is obtained. The reaction conditions are: the alkali is caustic soda, the amount of caustic soda is the theoretical amount of alkali required for the preparation of active silicon dioxide in the acid residue, the liquid-solid ratio is 4:1, the reaction temperature is 50℃, and the reaction time is 1h. The carbon content in the obtained alkaline residue is 80% wt, and the specific surface area is 160 m². 2The adsorption value of sodium silicate is 204 mg / g, and the adsorption value of methylene blue is 57 mg / g. The alkaline solution obtained after washing and separation is used to prepare water glass. The prepared water glass meets the requirements of GB / T 4209-2022 Industrial Sodium Silicate L-280-41 qualified products.
[0013] (3) Purification: Hydrofluoric acid was added to the alkaline residue to remove impurities and obtain activated carbon precursor. The reaction conditions were: liquid-to-solid ratio of 3-4:1, hydrofluoric acid amount of 0.6-1.1 times the theoretical acid amount, reaction temperature of 50-80℃, and reaction time of 20-40 min. The specific surface area of the activated carbon precursor obtained after purification was 200-230 m². 2 / g, iodine adsorption value is 216-240mg / g, methylene blue adsorption value is 70-90mg / g.
[0014] (4) Modification: The activated carbon precursor is modified with CO2 at high temperature to increase its specific surface area and mesopores, thereby obtaining activated carbon that meets the requirements of T / QGCML 205—2021 product standard; the reaction conditions are: temperature 700-1100℃, gas velocity 20-80mL / min, and reaction time 1-4h; the obtained activated carbon has a specific surface area ≥600m². 2 / g, iodine adsorption value ≥700mg / g, methylene blue adsorption value ≥135mg / g, pore volume ≥0.4ml / g
[0015] The coal gasification slag refers to the solid residue remaining after coal is gasified at high temperature to produce syngas, which is then quenched and cooled by water; its main minerals are amorphous and have good reactivity.
[0016] The technical principle of this invention is as follows:
[0017] The coal gasification temperature is above 1400℃, exceeding the ash melting temperature. At this temperature, the mineral composition forms corresponding salts. After rapid cooling with water, these salts do not crystallize quickly enough and are mainly amorphous, exhibiting good reactivity, thus providing conditions for multi-element extraction from coal gasification slag. After the coal gasification slag is reacted with hydrochloric acid, the main oxides, such as calcium, iron, aluminum, magnesium, and alkali metals, are transferred to the liquid phase and separated from the acid slag. The inorganic matter in the acid slag is mainly amorphous silica and a small amount of α-silica. After wet alkaline dissolution, all the amorphous silica and a small amount of α-silica are transferred to the liquid phase and separated from the alkaline slag. At this point, the carbon content in the alkaline slag is close to 90%, and the specific surface area after drying is approximately 149 m². 2 / g, it has a certain adsorption effect. After removing impurities with hydrofluoric acid, its carbon content can reach over 97wt%, and its specific surface area can reach 230m². 2 / g, the adsorption capacity was improved to some extent, but it still could not meet the requirements of the T / QGCML 205—2021 qualified product standard. At this time, it was subjected to surface modification and pore restructuring with CO2 at a certain temperature, and its specific surface area reached a maximum of 844m².2 / g, meeting the requirements of T / QGCML 205—2021 Grade I standard, can be widely used in the field of deep treatment of non-degradable color, odor, heavy metal ions and their complexes in wastewater, laying the foundation for the economic and feasibility of comprehensive utilization of coal gasification slag.
[0018] Figure 1 (a) and (b) are SEM images of alkali residue and activated carbon, respectively. As can be seen from the images, alkali residue exhibits a large, discontinuous shell-like cavity structure, while activated carbon after purification and modification exhibits a rich and interconnected honeycomb structure, proving that activated carbon with a rich pore structure was obtained.
[0019] Compared with existing technologies, this invention addresses the characteristics of high carbon content in coal gasification slag and the fact that the solid waste after inorganic mineral extraction is mainly composed of organic carbon. It increases the utilization value of solid waste after multi-element extraction of coal gasification slag, thereby improving the economic benefits of comprehensive utilization of coal gasification slag. The activated carbon prepared by this invention meets at least the requirements of the T / QGCML 205—2021 product standard, realizing solid waste reuse. This invention enhances the added value of multi-element extraction residue from coal gasification slag, ensuring the economic viability and feasibility of comprehensive resource utilization of coal gasification slag. Attached Figure Description
[0020] Figure 1 SEM images of alkaline residue and activated carbon;
[0021] in Figure 1 (a) is a SEM image of the alkali residue. Figure 1 (b) is a SEM image of activated carbon;
[0022] Figure 2 This is a process flow diagram for this application. Detailed Implementation
[0023] The present application will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited by the embodiments.
[0024] To more clearly describe the process of this invention, the characteristics of the coal gasification slag material, the acid-soluble extraction of acid-soluble substances, and the alkali-soluble silicon extraction process are briefly described below:
[0025] (1) Composition of raw materials for coal gasification slag
[0026] Table 1 Chemical Composition Analysis of Coal Gasification Slag Raw Materials
[0027] mass fraction / % 31.31 12.64 10.84 8.52 2.05 1.63 1.12 0.52 31.03
[0028] Theoretical acid (HCl) dosage calculation:
[0029] 0.52*1.827+8.52*1.37+10.84*2.148+12.64*1.3017+2.05*1.8112+1.12*0.7749+1.63*1.1778=58.86g;
[0030] That is, the theoretical acid required for 100g of coal gasification slag is 58.86g of HCl; which is equivalent to 162.26g of concentrated industrial hydrochloric acid.
[0031] (2) Acid dissolution reaction conditions and characteristics of coal gasification slag
[0032] Table 2. Conditions for acid dissolution reaction of coal gasification slag
[0033] Theoretical acid dosage 80℃ 3h 4:1
[0034] Table 3 Chemical composition analysis of acid residue
[0035] mass fraction / % 43.62 0.57 1.98 0.48 0.24 0.36 0.30 0.39 52.06
[0036] (3) Alkali dissolution reaction conditions and characteristics of alkali residue
[0037] The silica content in the acid residue was 43.62%, and analysis showed that the active silica content was 89.27%, meaning the active silica content in the acid residue was 38.94%.
[0038] Theoretical alkali usage calculation:
[0039] (80*38.94%*100) / (2.6*60.08)=19.94g;
[0040] That is, the theoretical alkali dosage required for 100g of coal gasification slag acid residue is 19.94g.
[0041] Table 4. Reaction conditions for acid residue and alkali dissolution
[0042] Theoretical alkali dosage 50℃ 1h 4:1
[0043] Table 5 Chemical composition analysis of alkaline residue
[0044] mass fraction / % 10.94 0.51 3.52 0.74 0.35 1.24 0.46 0.54 79.83
[0045] Table 6 Characteristics of Alkali Slag
[0046] <![CDATA[160m 2 / g]]> 204mg / g 57mg / g
[0047] (4) Calculation of theoretical hydrofluoric acid consumption for alkaline residue purification
[0048] 10.94*1.33+3.53*1.18+0.74*0.75+0.54*1.00+0.51*0.71+0.35*0.99+0.46*0.42+1.24*0.65=21.52g(HF);
[0049] That is, the theoretical acid required for 100g of alkaline residue is 21.52g of HF; which is equivalent to 53.80g of hydrofluoric acid with a mass fraction of 40%.
[0050] Example 1
[0051] The alkaline residue was treated with hydrofluoric acid for impurity removal. The reaction conditions were: liquid-to-solid ratio of 3:1, hydrofluoric acid dosage of 0.6 times the theoretical amount, reaction temperature of 50℃, and reaction time of 40 min. The relevant physical properties of the activated carbon precursor were analyzed as follows:
[0052] Table 7. Tests of relevant physical properties of activated carbon precursors in Example 1.
[0053] 90.2% <![CDATA[200m 2 / g]]> 216mg / g 70mg / g
[0054] The purified activated carbon precursor was placed in a tube furnace with CO2 exhaust air at 700℃, and CO2 gas was introduced at a flow rate of 80 mL / min for 1 hour of thermal activation. Heating was then stopped, and the mixture was cooled to room temperature under a CO2 atmosphere. The weight loss of the activated carbon precursor during the activation process was 4.47%. The product test results are shown in the table below:
[0055] Table 8 Technical Specifications for Activated Carbon Product Preparation in Example 1
[0056]
[0057] The prepared product's performance indicators were compared with those of activated carbon in T / QGCML 205-2021, and the prepared product met the requirements for qualified products.
[0058] Example 2
[0059] The alkaline residue was treated with hydrofluoric acid under the following conditions: liquid-to-solid ratio of 3.5:1, hydrofluoric acid dosage of 0.9 times the theoretical amount, reaction temperature of 60℃, and reaction time of 30 min. The relevant physical properties of the purified residue are shown below:
[0060] Table 9. Tests of relevant physical properties of activated carbon precursors in Example 2.
[0061] 95.5% <![CDATA[218m 2 / g]]> 229mg / g 82mg / g
[0062] The purified activated carbon precursor was placed in a tube furnace with CO2 exhaust air at 900℃, and CO2 gas was introduced at a flow rate of 50 mL / min for 3 hours of thermal activation. Heating was then stopped, and the mixture was cooled to room temperature under a CO2 atmosphere. The weight loss of the activated carbon precursor during the activation process was 8.32%. The product test results are shown in the table below:
[0063] Table 10 Technical Specifications for Activated Carbon Product Preparation in Example 2
[0064]
[0065]
[0066] The prepared product's performance indicators were compared with those of activated carbon in T / QGCML 205-2021, and the prepared product met the requirements for Grade I.
[0067] Example 3
[0068] The alkaline residue was treated with hydrofluoric acid under the following conditions: liquid-to-solid ratio of 4:1, hydrofluoric acid dosage of 1.1 times the theoretical amount, reaction temperature of 80℃, and reaction time of 20 min. The relevant physical properties of the purified residue are shown below:
[0069] Table 11. Physical property testing of activated carbon precursor in Example 3
[0070] 98.2% <![CDATA[230m 2 / g]]> 240mg / g 90mg / g
[0071] The purified activated carbon precursor was placed in a tube furnace with CO2 exhaust air at 1100℃, and CO2 gas was introduced at a flow rate of 20 mL / min for thermal activation for 4 hours. Heating was then stopped, and the mixture was cooled to room temperature under a CO2 atmosphere. The weight loss rate of the activated carbon precursor during the activation process was 9.23%. The product test results are shown in the table below:
[0072] Table 12 Technical Specifications for Activated Carbon Product Preparation in Example 3
[0073]
[0074]
[0075] The prepared product's performance indicators were compared with those of activated carbon in T / QGCML 205-2021, and the prepared product met the requirements for superior grade.
Claims
1. A method for preparing activated carbon from coal gasification slag, characterized in that, It includes the following steps: (1) Acid dissolution: calcium, iron, aluminum, magnesium and alkali metals in coal gasification slag are dissolved with hydrochloric acid, and acid slag is obtained by filtration, separation and washing. The reaction conditions for acid dissolution are as follows: hydrochloric acid is the theoretical amount of all acid-soluble substances in the gasification slag, the liquid-to-solid ratio is 4:1, the reaction temperature is 80℃, and the reaction time is 3h. (2) Alkali dissolution, adding alkali to the acid residue to react fully, so that most of the amorphous silicon and a small amount of α-type silicon oxide in the acid residue are transferred into the alkali solution, and then the alkali residue is obtained by separation and washing. The reaction conditions for alkali dissolution are as follows: the alkali used is caustic soda, the amount of caustic soda used is the theoretical amount of alkali used based on the set modulus of active silica preparation in the acid residue, the liquid-to-solid ratio is 4:1, the reaction temperature is 50℃, and the reaction time is 1h; the carbon content in the obtained alkali residue is 80wt%, and the specific surface area is 160m². 2 / g, iodine adsorption value is 204mg / g, methylene blue adsorption value is 57mg / g; The alkaline solution obtained after washing and separation is used to prepare water glass. The prepared water glass meets the requirements of GB / T 4209-2022 Industrial Sodium Silicate L-280-41 qualified products. (3) Purification: Hydrofluoric acid is added to the alkaline residue to remove impurities and obtain activated carbon precursor; The purification reaction conditions were as follows: liquid-to-solid ratio of 3-4:1, hydrofluoric acid amount of 0.6-1.1 times the theoretical acid volume, reaction temperature of 50-80℃, and reaction time of 20-40 min; the specific surface area of the purified activated carbon precursor was 200-230 m² / g. 2 / g, iodine adsorption value is 216-240mg / g, methylene blue adsorption value is 70-90mg / g; (4) Modification: The activated carbon precursor is modified with CO2 at high temperature to increase its specific surface area and mesopores, thereby obtaining activated carbon that meets the requirements of the T / QGCML205—2021 product standard. The modification conditions were: temperature 700-1100℃, gas velocity 20-80 mL / min, and reaction time 1-4 h; the obtained activated carbon had a specific surface area ≥600 m². 2 / g, iodine adsorption value ≥700mg / g, methylene blue adsorption value ≥135mg / g, pore volume ≥0.4ml / g; Coal gasification slag refers to the solid residue remaining after coal is gasified at high temperature to produce syngas, which is then quenched and cooled by water.
Citation Information
Patent Citations
Method for synthesizing adsorption material from fine coal gasification slag, and adsorption material prepared therethrough
CN107855103A
Method for preparing magnetic activated carbon NaX molecular sieve composite material by taking coal gasification fine slag as raw material
CN111715196A
A method for preparing activated carbon from coal gasification fine ash using a NaOH-HCl atmospheric pressure hydrothermal process.
CN115092926B
Method for preparing adsorbing material by utilizing fine coal gasification slag
CN115888673A
Granular coal gasification fine slag-based adsorbing material as well as preparation method and application thereof
CN116272848A